2016
DOI: 10.5409/wjcp.v5.i3.234
|View full text |Cite
|
Sign up to set email alerts
|

Reducing childhood obesity through coordinated care: Development of a park prescription program

Abstract: Major hindrances to controlling the current childhood obesity epidemic include access to prevention and/or treatment programs that are affordable, provide minimal barriers for participation, and are available to the general public. Moreover, successful childhood obesity prevention efforts will require coordinated partnerships in multiple sectors such as government, health care, school/afterschool, and the community but very few documented sustainable programs currently exist. Effective, community-based health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Making use of interventions such as social prescribing (referring patients to activities or programmes available within the community to improve their health and wellbeing; Bickerdike et al, 2017; Messiah et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Making use of interventions such as social prescribing (referring patients to activities or programmes available within the community to improve their health and wellbeing; Bickerdike et al, 2017; Messiah et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One approach currently gaining popularity is "park prescriptions", defined here as programs where clinicians prescribe or recommend park visits to encourage healthy, active living. In practice, these programs range from providers printing out maps of local parks [5], to partnerships with existing park programs [6], to health care providers leading park outings with patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 Yet, evidence suggests that youth, defined by the World Health Organization as children and adolescents 0–19 years, 4 , 5 are not meeting international physical activity guidelines, thereby contributing to poor health outcomes in childhood and later on in life. 1 , 6 - 8 Globally 80% of adolescents aged 11 to 17 do not meet the physical activity recommendations of at least 60 minutes per day of moderate-to-vigorous-intensity physical activity (MVPA), 9 and international studies of children from 3–6 years have found 21.2–35.6% of children do not engage in daily MVPA. 10 , 11 A recent evidence summary of physical activity studies for children and adolescents 5–17 years found that of the 21 systematic reviews evaluated, each review was geared towards interventions that impacted physical activity, yet there were limited reviews that examined the association between physical health and mental health for youth.…”
Section: Objectivementioning
confidence: 99%